Varietal diversity and conservation status of banana, taro, pumpkin, and mustard green in mountainous areas of Northwest Vietnam - Vu, D.T.; Ta, P.D.V.; Vu, T.D.; Naziri, D.; Le, T.M.T.; Vo, A.T.; Navarrete, I.; Haan, Stef de (2025)
This study assesses the agrobiodiversity richness, traditional knowledge, and conservation status associated with four key crops—banana, taro, pumpkin, and mustard green—in Northwest Vietnam. Using the 5-cell method, 133 farmer varieties were identified in Mai Son and Sa Pa districts. Mai Son showed the highest level of varietal diversity in banana and pumpkin, while Sa Pa had the higher richness in mustard green and taro. Ethnic groups, particularly Thai and Dao households, played a key role in maintaining this diversity. The findings reveal significant vulnerability to varietal loss, particularly for banana and taro. In contrast, pumpkin varieties in Sa Pa and mustard greens in both districts appear less vulnerable. Declining cultivation of certain farmer varieties is driven by changing preferences, market limitations, and climate variability. Results underscore the need for on-farm conservation strategies such as custodian farmer networks, biodiversity seed fairs, seed banks, improved market access, and nutritional education, to safeguard local varietal diversity and promote sustainable farming systems in the region.